Ab initio powder X-ray diffraction structural analysis of bispidine based 1D coordination polymers: insights into their guest responsive behaviour. Issue 44 (31st October 2019) - Lippi, Martina; Cametti, Massimo; Martí-Rujas, Javier
Abstract : The first ab initio synchrotron powder XRD structure solution of a desolvated 1D bispidine coordination polymer (CP) is reported, providing valuable insights into the stability, dynamic and guest responsive behavior of a new class of CPs. Abstract : The first ab initio synchrotron powder X-ray diffraction (XRD) data structure solution, employing real-space global optimization strategies followed by Rietveld refinement, was obtained for a bispidine based one-dimensional ribbon-like coordination polymer (CP) 1 . The structure solution of 1, a non-dynamic phase containing no solvent molecules, is crucial to obtain a more comprehensive view of the dynamic behaviour of a new family of 1D CPs, in terms of solvent adsorption and exchange processes by direct comparison among the structures, solvent–ribbon and inter-ribbon interactions of the CP materials. This work also reports novel bisolvated phases, 1·TCM· o NT, 1·TCM· p CT and 1·TCM·NB, in the form of single crystals and microcrystalline powders and shows that 1 can be thermally activated to regain dynamic selective adsorption features.